MENANAMKAN NILAI MODERASI BERAGAMA MELALUI MATA PELAJARAN PAI KELAS 6 DI SDN 08 SURO BALI - Nelson; Nurjannah; Nove Yuriska (CV. ALIM'SPUBLISHING, 2023)
The aims of this research are (1) to find out how PAI teachers instill the value of religious moderation through PAI subjects in class 6 of SDN 08 Suro Bali (2) to find out the supporting and inhibiting factors in instilling the value of religious moderation in class 6 of SDN 08 Suro Bali. The type of research used is qualitative research. The data sources in the research were Islamic religious education teachers and 6th grade students. The research instruments used were observation guidelines, interview guidelines and documentation. The data analysis techniques used are data reduction techniques, data presentation, and data verification. The research results found that religious moderation means a middle way of religion. With religious moderation, a person is not extreme and does not go to extremes when carrying out the teachings of his religion. Being moderate is enough to respect others and not disturb each other. (1) The way PAI teachers instill the value of religious moderation through PAI subjects in class 6 at SDN 08 Suro Bali is by using lecture, demonstration, discussion, question and answer and project assignment methods by providing understanding, experience, examples and material knowledge to the students. students, then creating an attitude of mutual respect and respect, not differentiating between students of different religions, ethnicities, races, cultures and religions, not differentiating between students' abilities when studying, educating students to always love and care for each other, prioritizing good deliberation or discussion in students, do not use violence, are always friendly, polite, behave well towards teachers and other friends.